10 Keys To Understanding Populist Propaganda In Latin America (Journal of Pharmaceutical Negative Results, 2023)
An analysis of the main characteristics that distinguish populist propaganda in Latin America is presented. There is a context of democratic immobility, in which the transition processes did not materialize in several nations, which has brought disinterest and institutional vacuums. Populism appears as an electoral offer that does not depend on a specific ideology but on aclaiming myth, which is always disruptive, anti-system, Manichaean and nationalist. When populism becomes a government, the project is embodied in a person who will try to modify the institutions to preserve their target.